Marketing analysis of ASABRI pension financing at the KCP Binjai National Pension Savings Bank (BTPN). - Sonia Dwi Putri (Indonesia Accounting Research Journal, 2021)
This study aims to determine the Marketing Analysis of Asabri Pension Funding at Bank BTPN KCP Binjai. This study uses a descriptive method using qualitative data. The results of this study indicate that the implementation of the provision of Asabri pension financing at Bank BTPN KCP Binjai was initially carried out with market segmentation first, then starting to determine targets, then determining positioning, and finally marketing mix. Obstacles in implementing the Asabri pension at Bank BTPN KCP Binjai, namely: a) The Asabri pension financing product at the BTPN Binjai Branch Office is still relatively new and many of the retirees who are new to implementing this financing product do not know about it, so they have to market this product intensively. b) Promotion through electronic media is not very effective because the prospective customers are elderly retirees. Marketing using websites or other social media is less effective so that much of the information conveyed via electronic media does not reach these pension financing customers. c) High competition which has more branch units in the regions and is also better known by retirees. d) The public still does not fully understand Islamic banking in terms of applications and products available in banks. This is a major obstacle for BTPN KCP Binjai. Supporting factors in the implementation of the Asabri pension at Bank BTPN KCP Binjai, namely: a) The process is easy and fast, b) Easy and fixed installments until paid off.